2016
DOI: 10.3389/fmicb.2016.00016
|View full text |Cite
|
Sign up to set email alerts
|

Aerobiology Over Antarctica – A New Initiative for Atmospheric Ecology

Abstract: The role of aerial dispersal in shaping patterns of biodiversity remains poorly understood, mainly due to a lack of coordinated efforts in gathering data at appropriate temporal and spatial scales. It has been long known that the rate of dispersal to an ecosystem can significantly influence ecosystem dynamics, and that aerial transport has been identified as an important source of biological input to remote locations. With the considerable effort devoted in recent decades to understanding atmospheric circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 30 publications
0
47
0
Order By: Relevance
“…The Dunde ice core data also showed one small cell density peak c2 appearing at the clean ice layer a2 in Figure 4 . These results indicate that microbial deposition in the glacier snow does not always associate with the dust deposits or “dirty” wind and may in fact be transported by “clean” wind or snow, which implies influences of the processes such as aerosol and precipitation deposition, along with other factors (Bottos et al, 2014; Pearce et al, 2016). …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The Dunde ice core data also showed one small cell density peak c2 appearing at the clean ice layer a2 in Figure 4 . These results indicate that microbial deposition in the glacier snow does not always associate with the dust deposits or “dirty” wind and may in fact be transported by “clean” wind or snow, which implies influences of the processes such as aerosol and precipitation deposition, along with other factors (Bottos et al, 2014; Pearce et al, 2016). …”
Section: Discussionmentioning
confidence: 95%
“…are common in both the Kuytun 51 and Qiangyong glaciers but only Rhodoferax ( Betaproteobacteria ) is dominant in the Kuytun 51 glacier (Xiang et al, 2010). The changes of the dominant bacteria in glaciers are mainly influenced by processes such as wind deposition (airborne or aerosol-associated microorganisms by prevailing winds and dust-associated microorganisms by dust storm events), precipitation deposition (microbial deposition with snow, wet-deposition), and post-deposition by microbial growth in the warming seasons on the glacier surface snow (Xiang et al, 2009; Price and Bay, 2012; Bottos et al, 2014; Peter et al, 2014; Meola et al, 2015; Miteva et al, 2015; Pearce et al, 2016). Among these processes, post-deposition has an important role in the transition of microbial communities in glaciers.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies in the Arctic region report high diversity, similar to levels observed in worldwide soils (Torsvik et al, 1996;Neufeld and Mohn, 2005;Lee et al, 2013), yet, no geographical region has been characterized as significantly harbouring higher diversity. Arctic soil diversity may increase due to inoculation from other environments such as snow cover or meltwater (Larose et al, 2010) or even through aerial dispersal (Pearce et al, 2016). Areas of convergence could be hotspots of diversity but may support many allochthonous organisms with little functional significance for the environment (Neufeld and Mohn, 2005).…”
Section: Importance Of Understanding Arctic Microbial Biogeographymentioning
confidence: 99%
“…Research has shown that diatoms can reach the atmosphere in various ways including volcanic eruptions (Pike, 2013;Van Eaton et al, 2013) and dust and sand storms (Griffin et al, 2002). Airborne diatom propagules have been collected by various methods from a variety of locations (Holzapfel, 1978;Vanormelingen et al, 2008;Pearce et al, 2016;Tesson et al, 2016).…”
Section: Diatomsmentioning
confidence: 99%